UJI EFEKTIVITAS DAYA HAMBAT PERTUMBUHAN JAMUR DERMATOFITA OLEH EKSTRAK BUAH NANAS - ABDUL RAZAK; MELVIANA LUBIS (LP2MTBM MAKARIOZ, 2020)
Fungal infections are the most common skin disease in tropical and developing countries. Fungal infections caused bydermatophytes such as Tricophyton. Pineapple (Ananas comosus L.) contains flavonoids, saponins and polyphenols as antifungi. This study aims to know whether pineapple extract has growth inhibition effect on dermatophytic fungi which causetinea corporis, in vitro. This is an experimental study with post test only design, consists of 4 group: two intervention group(Pineapple extract 10% and 25%), positive control and negative control group. Four sample sources were taken from newpatient with tinea corporis which then identified as Microsporum and Tricophyton.In these test Saboroud Dextrose Agarplates were used and growth inhibition effect was measured by clear zone. In this study, none of the groups shown clearzones. Pineapple extract 10% and 25% cannot inhibit the growth of dermatophytes in tinea corporis patients.